Reduction method of residual voltage by connecting lead length of surge protection device - Dal Kim, Young; Chan Kim, Young; Mi Jeong, Yun; Dong Lee, Dae (International Journal of Engineering and Technology, 2018)
Background/Objectives: In order to minimize the damage and malfunction of the equipment and system from various surges, we studied the method of reducing the residual voltage according to the lead wire length of the surge protector.Methods/Statistical analysis: In buildings, SPD installation space is insufficient or narrow, resulting in longer lead wire of SPD, and SPD protection performance is decreased due to increase of voltage protection level and residual voltage. In this study, the voltage protection level and the residual voltage of the conventional SPD model and the proposed SPD model are analyzed according to the change of the connecting conductor length from 0.5to 100m.Findings: In the case of the conventional SPD model, the protection level of the SPD is excellent by measuring the voltage protection level at 1,410V even if the lead wire length of the connecting conductor is changed to 10m, but when it exceeds 10m, the protection performance and the protection cooperation are reduced. On the other hand, in the case of the proposed SPD model, the voltage protection level was measured to be 50 V or less even if the lead wire length of the connecting conductor was changed to100 m. Therefore, it is considered that SPD protection performance and protection cooperation are excellent.Improvements/Applications: The design technique of SPD obtained through this study will help to select the optimal installation site and reduce the budget.Â Â